Fe3O4 Nanoparticles Attenuated Salmonella Infection in Chicken Liver Through Reactive Oxygen and Autophagy via PI3K/Akt/mTOR Signaling - Shen, Yiru; Xiao, Yunqi; Zhang, Shan; Wu, Shu; Gao, Lizeng; Shi, Shourong (Frontiers in Physiology, 2020)
Recently nanomaterials have received substantial attention in biotechnology sciences because of their novel physical and chemical functional properties. One of the most arrestive properties of nanomaterials that has been reported is their bacteriostatic activity. Our previous research found that Fe3O4 magnetic nanoparticles (Fe3O4-NPs) could effectively reduce the viability of intracellular Salmonella Enteritidis (S. Enteritidis) in chicken cells. There is an essential need to explore whether the bacteriostatic activity of Fe3O4-NPs is available in vivo. As an extension of this research, the present study was conducted to evaluate the potential effect of Fe3O4-NPs used for S. Enteritidis control in chickens and to extensively investigate the underlying mechanisms in the process. The overall study included the evaluation of pathological sections, antioxidant status, inflammation, and the autophagy status of chicken liver, including the PI3K/Akt/mTOR signaling pathway involved in the process. The results indicated that Fe3O4-NPs pretreatment can effectively inhibit the invasion of S. Enteritidis in chicken liver. Fe3O4-NPs pretreatment significantly increased reactive oxygen species (ROS) generation in chickens, including antioxidant enzyme activities. S. Enteritidis infection significantly increased the protein expression of the autophagy marker LC3. Additionally, the inflammation response and pathological changes caused by S. Enteritidis infection were alleviated by Fe3O4-NPs pretreatment. Phosphorylated mTOR was significantly increased in S. Enteritidis infected chickens, but showed no difference in chickens pretreated with Fe3O4-NPs. In summary, the results demonstrated that ROS and autophagy were involved in the inhibition of S. Enteritidis in chickens by Fe3O4-NPs pretreatment. The redox balance and inflammation response appeared normal in the process, as did the expression of the PI3K/Akt/mTOR signaling pathways. These results provide laboratory evidence not only for the safety evaluation and biomedical application of Fe3O4-NPs but also for the exploration of Fe3O4-NPs as an alternative to antibiotics for bacterial inhibition in chickens.